Effects of Match-Related Contextual Factors on Weekly Load Responses in Professional Brazilian Soccer Players - Cruz Goncalves, Luiz Guilherme (2020)
This study aimed to quantify the weekly training load distributions according to match location, opponent standard, and match outcome in professional soccer players. Rate-of-perceived-exertion-based training load (sRPE) and distance- and accelerometry-based measures were monitored daily during 52 training sessions and 11 matches performed by 23 players. Athletes who played >= 60 min during non-congested weeks were considered for data analysis. The training days close to away matches (e.g., one day before the match = MD-1) presented greater sRPE, distance-based volume measures, and mechanical work (player load) compared to the training days close to home matches (p= 0.001-0.002; effect size (ES) = medium-large). The most distant days of the home matches (e.g., five days before the match = MD-5) presented higher internal and external loads than before away matches (p= 0.002-0.003, ES = medium). Higher sRPE, distance-based volume measures, and mechanical work were found during the middle of the week (e.g., three days before the match, MD-3) before playing against bottom vs. medium-ranking teams (p= 0.001-0.01, ES = small-medium). These metrics were lower in MD-5 before matches against bottom vs. medium-ranking opponents (p= 0.001, ES = medium). Higher values of all external load measures were observed during the training session before winning matches (MD-1) compared to a draw or loss (p< 0.001-0.001, ES = medium-large). In conclusion, the training load distribution throughout the week varied considerably according to match-contextual factors.